The Taraxacum sect. Erythrosperma (Asteraceae, Cichorioideae) in Slovakia IV. Distribution of T. erythrospermum and synonymisation of T. slovacum - Dudáš, Matej; Kolarčik, Vladislav; Šuvada, Róbert; Vašut, Radim J. (Phytotaxa, 2024)
The group of lesser dandelions (Taraxacum sect. Erythrosperma) is represented by more than 215 species growing in mostly xerothermic habitats throughout Europe. The only known species with sexual reproduction in this section is the diploid T. erythrospermum. It occurs in southern parts of Europe and reaches its northern limit in central Europe. In this study, we aimed at a detailed mapping of the species distribution in Slovakia in order to understand the spatial distribution at its northern range limits. We found that it is the most common xerothermous species in Slovakia, growing on various substrates such as limestone, dolomite, travertine, volcanic rocks and sands, while it is less common on brown soils and ruderal biotopes. It is a characteristic species of the class Festuco-Brometea with an altitudinal range extending from 120 to 650 m above sea level. We delimited the northern distribution and documented its highest occurrence at approximately ca 1500 m a.s.l. Two taxa, T. slovacum and T. punctatum, were described from the territory of Slovakia and we discuss their relationships to T. erythrospermum, with which T. slovacum is synonymised here for the first time. We also present new data on the genome size of T. erythrospermum in Slovakia, which range from 1.529 to 1.604 pg with a mean of 1.554 pg (± 0.024 SD), and provide chorological data on a remarkable morphological variant with grey-coloured achenes.